Mapping Science Teacher Professionalism in Junior High Schools - Emilia Candrawati; Ratnaningsih Eko Sardjono; Ijang Rohman; Binar Kurnia Prahani; Yendi; Yusi Riksa Yustiana; Ade Elvia; Mellyta Uliyandari (South Sulawesi Education Development (SSED), 2025)
Teacher certification is a fulfillment of professional competence. In Bengkulu City, many junior high school science teachers are still uncertified. Therefore, mapping is needed to see the number of the junior high school science teachers who are certified and uncertified in Bengkulu City. This research uses descriptive qualitative methods through observation and interviews. The results showed that 109 junior high school science teachers in Bengkulu City are already certified and 65 are uncertified. There are 114 junior high school science teachers in Bengkulu City who are civil servants and 60 non-civil servants who teach in 47 junior high schools in Bengkulu City. Meanwhile, teachers who are called to join the in-service certification program must pass the Teacher Competency Test (UKG), which causes some teachers to fail to follow the next stage in the in-service teacher training program (PPG). Therefore, in order to fulfill the mandate of the Teachers and Lecturers Law 2015, it is recommended that the Bengkulu City Goverment and the Ministry of Education and Culture implement an accelerated teacher certification program to ensure that teachers are professional.